Aral Oasis as Potential Base for Development of the Tourism - Sultanova Dilshoda Namazovna; Suvonqulov Saydulla Makkamovich; Dusanov Zafar Zohirovich (Indonesian Journal of Law and Economics Review, 2020)
Given article is denoted of theoretical benchmark analysis - of geographical, climatic, ecologic, landscapes criteria’s of the nature of Aral oasis - as potential base for development of the tourism. It is studied, as particularly at Soviet period scientist seminal studied the Aral oasis at all points. It is given artistic analysis to Aral series of the artist in accompaniment with photo reproductions in 1959 year from works of painter. To enormous regret, the present-day youth nearly has not a full belief about fate Aral epidemic deaths. The examples is described about created card and scheme for forecasting of terrain of the town-port Muynak, created on miscellaneous method and already of needs in editions and addition last information. Row of the offers is given. In conclusion on the further development and improvement former Aral epidemic deaths, on inimitable of flora and fauna. The broad artistic analysis of the process is given in reconstruction of Aral museums in accompaniment with photo reproduction using work painter from 1960-2020. As a result of modern analyses with original museum of Aral Sea under opened by sky, as specific facility for development of the tourism is studied in our republic and have a questions, which expects their own decisions. The author is present for the first time in picturesque way in your attention, painting to interpretation, coming from it scientifically- creative experience. Given exploratory work, possible considers, as significant contribution to science in theories landscape architecture, archaeologies and history of art.